Getting to the bottom of L2 listening instruction: Making a case for bottom-up activities - Siegel, Joseph; Siegel, Aki (Studies in Second Language Learning and Teaching, 2015)
This paper argues for the incorporation of bottom-up activities for English as a foreign language (EFL) listening. It discusses theoretical concepts and pedagogic options for addressing bottom-up aural processing in the EFL classroom as well as how and why teachers may wish to include such activities in lessons. This discussion is augmented by a small-scale classroom-based research project that investigated six activities targeting learners’ bottom-up listening abilities. Learners studying at the lower-intermediate level of a compulsory EFL university course were divided into a treatment group (n = 21) and a contrast group (n = 32). Each group listened to the same audio material and completed listening activities from an assigned textbook. The treatment group also engaged in a set of six bottom-up listening activities using the same material. This quasi-experimental study used dictation and listening proficiency tests before and after the course. Between-group comparisons of t-test results of dictation and listening proficiency tests indicated that improvements for the treatment group were probably due to the BU intervention. In addition, results from a posttreatment survey suggested that learners value explicit bottom-up listening instruction.